Evaluation of Effective Microorganism (EM) for treatment of domestic sewage - Narendrakumar1; J. Arvind Kumar2, S. Karthick Raja Namsivayam1*, G. (Journal of Experimental Sciences, 2011)
Effective Microorganisms (EM), a culture ofÃ‚Â coexistingÃ‚Â beneficial microorganism predominantly consisting of lactic acid bacteria, photosynthetic bacteria, yeast, fermenting fungi and actinomycetes that are claimed to enhance microbial turnover in soil and thus known increase soil macronutrients and increases plant growth and yield. and treatment of sewages or effluents. In the present study the EM formulation was evaluated for reduction of of Alkalinity, Total dissolved solids, Biological oxygen demand, and Chemical oxygen demand of domestic sewage under standard condition.Ã‚Â All the parameters that were tested showed distinct reduction. But total hetrototropic bacterial and yeast population was increased. No change in fungal and actinomycetes population was recorded.The result of the experiment shows that EM has the potential to improve the effectiveness of treatment of domestic wastes.